State-Wise Public Expenditure on Higher Education in India : An Empirical Analysis - Jana, Sebak Kumar; Maiti, Adwaita (Arthshastra Indian Journal of Economics & Research, 2019)
Public expenditure is a major component of education expenditure in India. Though the higher-education expenditure in India increased significantly after Independence, budgetary allocations to higher education were squeezed off in the post economic reforms period and this sector also suffered significantly. The proportionate spending on the higher-education sector in India is much below the Central Advisory Board of Education (CABE) committee recommendation of 1% of gross domestic product for general higher education. The present study aimed to analyze state-wise disparity in public higher education expenditure in India by different parameters like per capita and per student higher education expenditure in terms of plan and non expenditure as well as revenue and capital expenditure. The regression results revealed that many states had elasticity of higher-education expenditure to gross state domestic product (GSDP) less than unity. Central and state governments of India should implement policies for more funding in the higher-education sector.